Zachowania zdrowotne kobiet w ciąży w kontekście zdrowia i rozwoju noworodka = Pro-health behaviours of pregnant women in the context of newborns` health and development - Kaiser, Alicja; Sokołowski, Marek; Kaiser, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The promotion of procreation health care should be directed at shaping responsibility in future mothers concerning their own and their offspring`s health as well as at preparing women to the social role of mothers. Actions should still be taken concerning elimination of risk factors that are responsible for premature birth as well as actions focused on educating future mothers about family planning and proper approach to pregnancy and motherhood.
Keywords: family health; pregnant woman; premature birth; pro-health behaviour; health promotion; ontogenesis; zdrowie rodziny; kobieta w ciąży; przedwczesny poród; zachowania prozdrowotne; promocja zdrowia; ontogeneza